Signature Pedagogies for Professions in Arts and Design Issues, Methods, Contexts, and Practices - Kan, Rebecca Y. P.; Khoo, Christopher S. G.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2025)
This open access book surveys the dynamic landscape of professional arts and design education research, examining salient concepts and issues through the lens of signature pedagogies as an analytical framework. The arts and design professions covered in this book are: music, dance, theatre, fashion design, design and media, and fine art. Chapters in the book present a combination of reflective accounts, in-depth analyses, and empirical research findings, shedding light on the education of students for productive and meaningful careers in the arts and design. They examine how concepts, issues, methods, and practices relate to habits of the mind, hand, and heart. Pedagogical insights on creative uncertainty, designerly formations, evocative ambiguity, generative apprenticeship, reflexivity, transition, truth, and artistic tradition and heritage are explored with nuance and depth. The book constitutes a collective effort of artist-educators at the Nanyang Academy of Fine Arts, University of the Arts Singapore, in documenting a shared institutional heritage, which is continually rejuvenated through critical engagement with contemporary challenges. They examine the tensions embedded in the signature pedagogies and possible solutions to address them at the micro- (e.g. classroom or practicum), meso- (e.g. program), and macro- (e.g. institution) levels. In the process, the book highlights research issues and directions for arts education researchers, while also offering ideas that artist-educators can explore and incorporate into their teaching.
1. Signature Pedagogies for Professional Arts and Design Education: The Setting, The Questions and Recurrent Themes -- 2. (3z(BIt$1 (Bs not about making beautiful sound. It$1 (Bs about making relevant sound to life(3y(B: Insights from a Veteran Artist-Educator in Music, Lim Yau -- 3. Codetta: Pedagogies of Pioneers in the Profession -- 4. The Convergence of Traditional and Cognitive Apprenticeship as a Signature Pedagogy: A Case Study of Dance Choreographer, Lim Fei Shen -- 5. Codetta: Pedagogies of Generative Apprenticeship.s
Accessibility summary: This PDF does not fully comply with PDF/UA standards, but does feature limited screen reader support, described non-text content (images, graphs), bookmarks for easy navigation and searchable, selectable text. Users of assistive technologies may experience difficulty navigating or interpreting content in this document. We recognize the importance of accessibility, and we welcome queries about accessibility for any of our products. If you have a question or an access need, please get in touch with us at accessibilitysupport@springernature.com.
No reading system accessibility options actively disabled
Publisher contact for further accessibility information: accessibilitysupport@springernature.com
Keywords: Art -- Study and teaching; Teaching; Education, Higher; Professional education; Vocational education; Teachers -- Training of; Education -- Research; Creativity and Arts Education; Pedagogy; Higher Education; Professional and Vocational Education; Teaching and Teacher Education; Educational Research